China's international investment strategy : bilateral, regional, and global law and policy - Chaisse, Julien (Oxford : Oxford University Press, 2019)
This volume explores the three tracks of China's investment policy and strategy: bilateral agreements, regional agreements, and global initiatives. Its overarching topic is whether these three tracks compete with or complement one another - a question of profound importance for China's political and economic future and world investment governance.
This edition previously issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on March 14, 2019).
Keywords: China -- Economic policy; China -- Economic conditions; China -- Foreign economic relations; Industry; Industry & industrial studies